1992
DOI: 10.1111/j.1440-1746.1992.tb01032.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary hypertrophic pyloric stenosis in the adult

Abstract: A case is reported of a 55 year old male patient with primary hypertrophic pyloric stenosis who was subjected to distal gastrectomy. Adult hypertrophic pyloric stenosis is an uncommon condition which is usually misdiagnosed as carcinoma of the antrum. It is a benign disease resulting from hypertrophy of the circular fibres of the pyloric canal and is recognizable radiologically by narrowing and elongation of the pyloric canal and endoscopically by appearances resembling those of the cervix. This condition is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A mild form of congenital pyloric stenosis may occasionally present later in adult life. 1 The exact occurrence of this form cannot be estimated accurately, since the majority of these patients are asymptomatic for years. Zavala et al 2 reported on a family with both congenital and adult type of hypertrophic pyloric stenosis.…”
Section: Adult Idiopathic Hypertrophic Pyloric Stenosismentioning
confidence: 99%
“…A mild form of congenital pyloric stenosis may occasionally present later in adult life. 1 The exact occurrence of this form cannot be estimated accurately, since the majority of these patients are asymptomatic for years. Zavala et al 2 reported on a family with both congenital and adult type of hypertrophic pyloric stenosis.…”
Section: Adult Idiopathic Hypertrophic Pyloric Stenosismentioning
confidence: 99%
“…On endoscopic finding, torus hyperplasia reveals as submucosal tumor since it arise from circular muscle consisting the pyloric canal which makes it hard to diagnose through endoscopic biopsy (6, 8). In addition, it is usually misdiagnosed as carcinoma of the antrum (6). Although recent progress of endoscopic ultrasonography and endoscopic resection had been made, it is hard to diagnose only with the aid of endoscopic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of the symptoms, no clinical treatment is required, and resection is advocated only when stenosis gives rise to symptoms or when a malignancy is suspicious (6, 8). Although endoscopic dilatation or laparascopic hypertrophy have been reported as alternative treatments (9, 10), distal gastrectomy with gastroduodenostomy is still the main therapy for final diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its clinical manifestations usually become obvious during the first 2 months of life [1] . The presence of pyloric stenosis in adults with characteristics of hypertrophy of the circular muscle layer of the pyloric canal is classified as primary hypertrophic pyloric stenosis and it is considered a mild form of congenital pyloric stenosis revealed in adult life [2] .…”
Section: Introductionmentioning
confidence: 99%